Menciptakan Ruang Digital Sehat: Program Pencegahan Cyberbullying bagi Remaja - Syarifudin, Aziz; Ahadiyah S, Elga Ignazha; Sepya , Eva Aulia; Alfaris, Muhammad Reza Dwiki; Alif, M.Rizal; Ardiningrum, Nadia; Pebriyanti, Putri; Salsabila, Safhira; Saputra, Wahyu; Abidin, Zainal (NAJWA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
The rapid development of digital technology has brought both positive and negative impacts to society, particularly among adolescents. One of the increasingly concerning negative impacts is the phenomenon of cyberbullying, which can cause serious psychological effects on its victims. Adolescents in Sitimerto Village, Pagu District, Kediri Regency still have a limited understanding of digital literacy and cyberbullying prevention. This community service program aims to increase adolescents' awareness and understanding of safe digital technology use and cyberbullying prevention through community-based digital education. The method used is the ABCD (Asset-Based Community Development) approach integrated with the Appreciative Inquiry approach, employing counseling techniques, interactive discussions, and practical workshops involving local adolescents. The program was implemented through a series of activities including asset identification, collective dream formulation, development of understanding regarding social media ethics, and program evaluation. The results showed an increase in participants' understanding of digital literacy and the dangers of cyberbullying. Participants demonstrated high enthusiasm and good ability in identifying forms of cyberbullying and prevention strategies. In conclusion, the digital education program is effective in increasing adolescents' awareness about responsible digital technology use and cyberbullying prevention in rural environments.